Management of Inorganic Fertilizer Raw Materials PT Citra Sawit Indah Lestasi using EOQ - Siregar, Dailami Dasuki; Lubis, Rizky Fauziah; Muhazir, Ahmad (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
PT Citra Sawit Indah Lestari is a business operating in the oil palm plantation sector. Based on initial observations, it turns out that the supply of inorganic fertilizer raw materials at PT Citra Sawit Indah Lestari has not been planned properly so that one time the raw materials run out during the production process, it often happens that excess orders for inorganic fertilizer raw materials result in the raw materials not being able to be used. . And the storage warehouse is full, which will disrupt the operations of raw material collection by employees. The aim of this research is to apply Economic Order Quantity (EOQ) in controlling inorganic fertilizer raw materials at PT Citra Sawit Indah Lestari to maintain the stability of oil palm fruit production. The research method used in this research is qualitative research. The results of this research are that the system designed is in accordance with the needs of PT Citra Sawit Indah Lestari and makes work easier in controlling inorganic fertilizer raw materials. The conclusion is that the application of the Economic Order Quantity method in managing the supply of inorganic fertilizer raw materials at the web-based PT Citra Sawit Indah Lestari makes it easier for business owners to manage fertilizer supplies well so that it is easier to order goods in the next period.